Effect of Sectioning of the Anterior Cruciate Ligament and Posterolateral Structures on Lateral Compartment Gapping: A Randomized Biomechanical Study. Issue 6 (6th June 2022) - Gursoy, Safa; Perry, Allison K.; Dandu, Navya; Singh, Harsh; Vadhera, Amar S.; Yanke, Adam; LaPrade, Robert F.; Chahla, Jorge
Background: The contribution of anterior cruciate ligament (ACL) injury to lateral instability under varus stress, particularly compared with posterolateral structures, is not well known. Purpose: To investigate the effect of sectioning the ACL and posterolateral knee structures on lateral compartment gapping under varus stress. Study Design: Controlled laboratory study. Methods: Fourteen nonpaired cadaveric knees were randomized to 1 of 2 groups: sequential sectioning of the ACL, fibular collateral ligament (FCL), popliteus tendon (PLT), and popliteofibular ligament (PFL) (ACL-first group) or sequential sectioning of the FCL, PLT, PFL, and ACL (FCL-first group). Knees were loaded onto a custom jig at a 20° flexion angle. A standardized 12-N·m varus moment was applied to each specimen in the intact state and after each randomized sequential-sectioning state. Lateral compartment opening was measured on radiographs to assess the contribution to the increase in the lateral gap caused by resecting the respective structure. The distance was measured by 3 observers on 15 images (5 testing states each imaged 3 times) per specimen, for a total of 210 radiographs. The articular cartilage surfaces were not included in the measurements. Results: The mean increase in lateral opening after sectioning all structures (ACL and posterolateral corner) was 4.6 ± 1.8 mm (range, 1.9-7.7 mm). The ACL and FCL sectioning contributed the most to lateral knee opening (1.3 ± 0.6 and 2.2 ± 1.3 mm, respectively). In both groups, lateral gapping >3 mm was achieved only after both the ACL and FCL were sectioned. All comparisons of increased mean gapping distances demonstrated a significant difference with subsequent sequential sectioning of structures, except comparisons between the FCL and PLT and the PLT and PFL. When considering the effect of the ACL on lateral opening, no significant difference was found between sectioning the ACL first or FCL first ( P = .387). Conclusion: ACL deficiency significantly increased lateral opening under varus stress, regardless of the sequence of injury. The effect of injury to the ACL in addition to the lateral structures should be considered when using varus stress radiographs to evaluate knee injuries. Clinical Relevance: With the current findings, understanding the effect of ACL and posterolateral corner injuries on lateral gapping under varus stress can aid in correctly diagnosing knee injuries and determining appropriate treatment plans.